Safety and efficacy of a prescription digital therapeutic as an adjunct to buprenorphine for treatment of opioid use disorder. (1st February 2021) - Maricich, Yuri A.; Bickel, Warren K.; Marsch, Lisa A.; Gatchalian, Kirstin; Botbyl, Jeffrey; Luderer, Hilary F.
Abstract: Objectives: To evaluate the safety and efficacy of a digital therapeutic in treatment-seeking individuals with opioid use disorder (OUD) in an analysis of randomized clinical trial (RCT) data (ClinicalTrials.gov identifier: NCT00929253). Methods: Secondary analysis of an RCT including 170 adults meeting DSM-IV criteria for OUD. Participants were randomized to 12-weeks of treatment-as-usual (TAU) or TAU plus a digital therapeutic providing 67 digital, interactive educational modules based on the Community Reinforcement Approach. TAU consisted of buprenorphine maintenance therapy, 30 min biweekly clinician interaction, and abstinence-based contingency management. Primary endpoints were treatment retention and abstinence (negative urine drug screen) during weeks 9–12 of treatment. Safety was assessed by evaluating adverse events. Results: Participants randomized to TAU plus a digital therapeutic had significantly greater odds of opioid abstinence during weeks 9–12 compared to TAU: 77.3 versus 62.1%, respectively ( p =.02), OR 2.08, 95% CI 1.10–3.95. The risk of patients leaving treatment was significantly lower in the digital therapeutic group (HR 0.49, 95% CI 0.26–0.92). No significant difference was observed in the rate of adverse events between groups ( p= .42). Conclusions: A prescription digital therapeutic (PDT) in combination with buprenorphine therapy improves clinically significant patient outcomes including abstinence from illicit opioids and retention in treatment compared with treatment as usual.